Kajian Jenis-Jenis Kalimat Dalam Sintaksis: Studi Kasus Pada Film Dora And The Lost City Of Gold - Saadah, Siti Waliyatus (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2023)
This study aims to understand the types of sentences in language learning because it can help learners understand how to build and use sentences correctly and effectively. In addition, understanding sentence types can also help enrich vocabulary and sentence structures used in daily communication. In this study, the film "Dora and The Lost City of Gold" is chosen as the subject, and the researcher aims to observe and analyze how each type of sentence is used in the film. By studying the types of sentences used in the movie, the researcher hopes to contribute to the development of film theory and practice, especially in the use of effective and efficient language in building a story. This research uses a descriptive qualitative research method used to analyze qualitative data and describe it in detail. The data collection technique used is the basic listening method followed by more advanced note-taking techniques. The syntactic approach in language is used to study the structure and pattern of sentences, clauses, phrases, and words in a language. The collected data were analyzed through qualitative analysis techniques, which involved data compaction, data presentation, and conclusion drawing and verification. The results of this study reveal that there are five types of sentences used in the movie "Dora and The Lost City of Gold", namely affirmative sentences 4 data, negative sentences 14 data, interrogative sentences 6 data, imperative sentences 8 data, and exclamation sentences 2 data.